Pteromalidae (Hymenoptera: Chalcidoidea) associated with plant galls in the south-eastern Iran, with three new records - Marziyeh Mahdavi; Seyed Massoud Madjdzadeh; Mircea-Dan Mitroiu (Journal of Insect Biodiversity and Systematics, 2015)
Six species of pteromalid wasps associated with plant galls, Rosa beggeriana Schrenk,  Ephedra major Host and Salix pycnostachya Andersson were collected from Kerman province, during 2010-2011. The identified wasps belong to four genera: Caenacis Förster, 1856, Gastrancistrus  Westwood, 1833, Mesopolobus Westwood, 1833, and Pteromalus Swederus, 1795. Three species are newly recorded for the Iranian fauna: Gastrancistrus ephedrae Dzhanokmen, 1994 (Pireninae), Pteromalus cyniphidis (Linnaeus, 1758) and P. dolichurus (Thomson, 1878) (Pteromalinae). Gastrancistrus ephedrae is associated with an unknown species of insect on E. major, P. bedeguaris (Thomson, 1878) with Diplolepis fructuum (Rübsaamen, 1882) (Hym.: Cynipidae) on R. beggeriana, P. cyniphidis and P. dolichurus with an unknown species of insect in leaf galls on S. pycnostachya, and Caenacis cf. inflexa and Mesopolobus sericeus with D. fructuum on R. beggeriana. Three new biological associations were found: M. sericeus with D. fructuum, and P. cyniphidis and P. dolichurus with S. pycnostachya. Short taxonomic comments, hosts and geographical distribution of the species are briefly mentioned.